Characteristics of Hadith Studies in the Era of Covid-19 Pandemic in Indonesia - Ade Pahrudin (Millati: Journal of Islamic Studies and Humanities, 2021)
This study aims to determine the characteristics of hadith studies in Indonesia during the Covid-19 pandemic. This study indicates that the study of hadith in Indonesia in particular and the study of Islamic studies, in general, are currently leading to digital scientific studies and development. The pandemic situation in the last two years that has changed the pattern of life from traditional to digital has further strengthened digitalization in Islamic science, especially the study of hadith. Thematic studies of hadith still dominate hadith studies during the pandemic. Hadith researchers have shifted from the tendency to write about studies on the development of Indonesian hadith towards studies related to the Covid-19 pandemic from the perspective of hadith as a form of sensitivity and concern for pandemic conditions in Indonesia. Four hadith thematic study articles respond to the current pandemic situation. This research is qualitative-descriptive-analytic by making scientific e-articles about hadith on the Moraref portal as the object of study.